Sizing agent for reinforcing fibers and reinforcing fibers
A sizing agent with alicyclic diol and alicyclic dicarboxylic acid residues, along with an alkali metal salt of 5-sulfoisophthalic acid, addresses roller contamination and enhances cohesiveness and adhesion in reinforcing fibers.
Patent Information
- Application Number
- JP2023095645
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-09
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2043-06-09
AI Technical Summary
Existing sizing agents for reinforcing fibers improve cohesiveness but fail to address the issue of roller contamination during application and do not enhance operational efficiency.
A sizing agent containing alicyclic diol and alicyclic dicarboxylic acid residues, along with an alkali metal salt of 5-sulfoisophthalic acid, is used to enhance cohesiveness and prevent roller contamination, featuring a specific concentration of sodium in the nonvolatile matter.
The solution provides improved cohesiveness and prevents roller contamination, ensuring smooth operation and enhanced adhesion to matrix resins.
Smart Images

Figure 2024176825000001 
Figure 2024176825000002 
Figure 2024176825000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a sizing agent for reinforcing fibers and to reinforcing fibers. [Background technology]
[0002] A sizing agent is a chemical applied to fiber materials such as carbon fibers, and is used for purposes such as suppressing damage to the fiber material and increasing the bundling ability of the fiber material. For example, JP 2018-90927 A (Patent Document 1) discloses a fiber sizing agent composition (sizing agent) containing a polyester resin and a polyether-based polymer. The invention described in Patent Document 1 is capable of imparting good bundling ability and openability to fiber bundles by satisfying certain conditions regarding the monomer composition of the polyester resin, the polymer type of the polyether-based polymer, and the weight ratio of the polyester resin to the polyether-based polymer. 。 [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2018-90927 A Summary of the Invention [Problem to be solved by the invention]
[0004] The invention described in Patent Document 1 is advantageous in that it can impart good bundling properties to fiber materials, but there is room for improvement in the productivity of sized fiber materials. In particular, sufficient consideration has not been given to preventing contamination of rollers that come into contact with fiber materials to which a sizing agent has been applied, thereby improving operability.
[0005] Therefore, there is a need to develop a sizing agent for reinforcing fibers and reinforcing fibers that can impart bundling properties to fiber materials and prevent contamination of rollers when the sizing agent is applied. [Means for solving the problem]
[0006] The sizing agent for reinforcing fibers according to the present invention comprises a polyester resin (A) having in its molecule at least one residue selected from a residue of an alicyclic diol and a residue of an alicyclic dicarboxylic acid, and a residue of an alkali metal salt of 5-sulfoisophthalic acid. a nonionic surfactant (B); and an epoxy resin (C); Contains The alkali metal salt of 5-sulfoisophthalic acid is sodium salt of 5-sulfoisophthalic acid, and the sodium element concentration in the non-volatile matter is 100 ppm or more and 8000 ppm or less. It is characterized by:
[0007] The reinforcing fiber according to the present invention is characterized in that the above-mentioned sizing agent for reinforcing fibers is adhered thereto.
[0008] These configurations make it possible to realize a sizing agent for reinforcing fibers and reinforcing fibers that can impart bundling properties to the fiber material and prevent contamination of the roller when the sizing agent is applied. In addition, it is easy to obtain a sizing agent for reinforcing fibers that has good adhesion to the matrix resin, and is also suitable from the viewpoint of increasing the adhesion of the sizing agent to the fiber material.
[0009] Preferred embodiments of the present invention will be described below. However, the scope of the present invention is not limited to the preferred embodiments described below.
[0010] In one embodiment of the sizing agent for reinforcing fibers according to the present invention, the polyester resin (A) preferably has a residue of an alicyclic diol in the molecule.
[0011] This configuration makes it easier to prevent the rollers from becoming contaminated.
[0012] In one embodiment of the sizing agent for reinforcing fibers according to the present invention, the content of the polyester resin (A) in the nonvolatile matter is preferably 5% by mass or more and 95% by mass or less.
[0013] This configuration makes it easy to achieve both bundling properties and prevention of roller contamination.
[0014] In one embodiment of the sizing agent for reinforcing fibers according to the present invention, the proportion of the mass of the polyester resin (A) to the total mass of the polyester resin (A) and the nonionic surfactant (B) is preferably 5% or more and 97% or less.
[0015] This configuration makes it easy to achieve both bundling properties and prevention of roller contamination.
[0016] In one embodiment, the sizing agent for reinforcing fibers according to the present invention is such that, relative to the total mass of the polyester resin (A), the nonionic surfactant (B), and the epoxy resin (C), the proportion of the mass of the polyester resin (A) is 5 mass% or more and 95 mass% or less, the proportion of the mass of the nonionic surfactant (B) is 2 mass% or more and 50 mass% or less, and the proportion of the mass of the epoxy resin (C) is 2 mass% or more and 65 mass% or less.
[0017] This configuration makes it easy to achieve high levels of bundling ability, prevention of roller contamination, and adhesion to fiber materials.
[0018] In one embodiment, the reinforcing fiber according to the present invention is preferably an inorganic fiber having the sizing agent for reinforcing fiber attached thereto.
[0019] According to this configuration, the present invention can be easily applied to reinforce composite materials whose base material is resin, ceramic, metal, or the like.
[0020] In one embodiment of the reinforcing fiber according to the present invention, the inorganic fiber is preferably a carbon fiber or a glass fiber.
[0021] This configuration makes the present invention particularly applicable to the reinforcement of composite materials whose matrix is resin, ceramic, metal, or the like.
[0022] Further features and advantages of the present invention will become more apparent from the following description of illustrative and non-limiting embodiments. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] The embodiment of the sizing agent for reinforcing fibers and reinforcing fibers according to the present invention will be described below. In the following, an example in which the sizing agent for reinforcing fibers according to the present invention (hereinafter simply referred to as "sizing agent") is applied to a sizing treatment of a fiber material will be described.
[0024] [Configuration of sizing agent] The sizing agent according to the present embodiment contains a polyester resin (A) as a non-volatile component. In addition, examples of non-volatile components that may be optionally contained in the sizing agent include a non-ionic surfactant (B) and an epoxy resin (C).
[0025] (polyester resin) The content of polyester resin (A) in the non-volatile content of the sizing agent is preferably 5% by mass or more and 95% by mass or less. When the content of polyester resin (A) in the non-volatile content is 5% by mass or more, the bundling property of the fiber material after the sizing treatment is likely to be good. In addition, when the content of polyester resin (A) in the non-volatile content is 95% by mass or less, contamination of the roller that comes into contact with the fiber material immediately after being removed from the sizing bath is likely to be suppressed. The non-volatile content of the sizing agent refers to the components that remain without volatilization after the sizing agent is heated in a hot air dryer at 105°C for 2 hours.
[0026] The polyester resin (A) according to this embodiment is a copolymer of a diol monomer and a dicarboxylic acid monomer. Therefore, the polyester resin (A) has, in its molecule, a diol residue, which is a partial structure derived from a diol monomer (a diol compound or a derivative thereof), and a dicarboxylic acid residue, which is a partial structure derived from a dicarboxylic acid monomer (a dicarboxylic acid or a derivative thereof). The composition of the polyester resin (A) is specified by the ratio (molar ratio) of the monomers constituting the molecule.
[0027] The polyester resin (A) according to the present embodiment has at least one residue selected from a residue of an alicyclic diol and a residue of an alicyclic dicarboxylic acid, and a residue of an alkali metal salt of 5-sulfoisophthalic acid in the molecule. Among these, the residue of the alicyclic diol is a diol residue, and the residue of the alicyclic dicarboxylic acid and the residue of the alkali metal salt of 5-sulfoisophthalic acid are dicarboxylic acid residues. It is preferable that the polyester resin (A) has a residue of an alicyclic diol.
[0028] The polyester resin (A) containing the residue of an alicyclic diol is obtained by using an alicyclic diol compound as a diol monomer. Here, the alicyclic diol compound refers to a compound having two hydroxyl groups and at least one alicyclic group in the molecule. Here, the hydroxyl group may be directly bonded to the alicyclic group, or may be indirectly bonded via another functional group. In addition, the carbon atoms to which the hydroxyl groups in the alicyclic group are directly or indirectly bonded may be different carbon atoms or the same carbon atom, but it is preferable that they are different carbon atoms.
[0029] The number of carbon atoms of the alicyclic group contained in the molecule of the alicyclic diol compound is not particularly limited, but may be, for example, 5 to 10. Therefore, examples of the alicyclic diol compound include 1,4-cyclohexanedimethanol (formula (1)), 1,4-cyclohexanediol, 1,2-cyclohexanediol, and 1,3-cyclopentanediol. When the polyester resin (A) contains a residue of an alicyclic diol in the molecule, the ratio of the alicyclic diol compound in the monomers constituting the polyester resin (A) is not particularly limited, but may be, for example, 1 mol % to 10 mol %. [ka]
[0030] The residue of the alicyclic diol is a residue derived from the above alicyclic diol compound. Therefore, the residue of the alicyclic diol contains an alicyclic group. In a preferred embodiment in which the carbon atoms to which the hydroxyl groups are directly or indirectly connected in the alicyclic group are different carbon atoms, the alicyclic group is contained in the polymer main chain of the polyester resin (A). As an example, the residue of the alicyclic diol derived from 1,4-cyclohexanedimethanol (formula (1)) as a diol monomer is shown in formula (2). [ka]
[0031] The diol monomer constituting the polyester resin (A) may contain one or more types of diol compounds other than the alicyclic diol compound (hereinafter referred to as "other diol compounds"). Examples of the other diol compounds include ethylene glycol, diethylene glycol, propylene glycol, and 1,4-butanediol. The ratio of the other diol compounds in the monomers constituting the polyester resin (A) is not particularly limited, but may be, for example, 40 mol% or more and 50 mol% or less. In addition, when the diol monomer contains multiple types of other diol compounds, the ratio of the other diol compounds referred to here is the total ratio of the multiple types of other diol compounds.
[0032] The polyester resin (A) containing the residue of an alicyclic dicarboxylic acid is obtained by using an alicyclic dicarboxylic acid compound or a derivative thereof as a dicarboxylic acid monomer. Here, the alicyclic dicarboxylic acid compound refers to a compound having two carboxy groups and at least one alicyclic group in the molecule, and the derivative refers to an acid anhydride, an ester, a metal salt, etc. of the alicyclic dicarboxylic acid compound. Here, the carboxy group may be directly bonded to the alicyclic group, or may be indirectly bonded via another functional group. In addition, the carbon atoms to which the carboxy groups in the alicyclic group are directly or indirectly bonded may be different carbon atoms or the same carbon atom, but it is preferable that they are different carbon atoms.
[0033] The number of carbon atoms of the alicyclic group contained in the molecule of the alicyclic dicarboxylic acid compound is not particularly limited, but may be, for example, 6 to 12. Therefore, examples of the alicyclic dicarboxylic acid compound include 1,4-cyclohexanedicarboxylic acid (formula (3)), 1,2-cyclohexanedicarboxylic acid, and dimethyl 1,4-cyclohexanedicarboxylate. When the polyester resin (A) contains a residue of an alicyclic dicarboxylic acid in the molecule, the ratio of the alicyclic dicarboxylic acid compound in the monomers constituting the polyester resin (A) is not particularly limited, but may be, for example, 1 mol % to 10 mol %. [ka]
[0034] The residue of the alicyclic dicarboxylic acid is a residue derived from the above alicyclic dicarboxylic acid compound. Therefore, the residue of the alicyclic dicarboxylic acid contains an alicyclic group. In a preferred embodiment in which the carbon atoms to which the carboxyl groups are directly or indirectly connected in the alicyclic group are different carbon atoms, the alicyclic group is contained in the polymer main chain of the polyester resin (A). As an example, the residue of the alicyclic dicarboxylic acid derived from 1,4-cyclohexanedicarboxylic acid (formula (3)) as a dicarboxylic acid monomer is shown in formula (4). [ka]
[0035] The polyester resin (A) containing the residue of 5-sulfoisophthalic acid alkali metal salt is obtained by using 5-sulfoisophthalic acid alkali metal salt as a dicarboxylic acid monomer. The 5-sulfoisophthalic acid alkali metal salt may be a sodium salt, a potassium salt, a lithium salt, etc., but is preferably a sodium salt. As an example, the residue of 5-sulfoisophthalic acid alkali metal salt derived from 5-sulfoisophthalic acid sodium salt as a dicarboxylic acid monomer is shown in formula (5). [ka]
[0036] When the alkali metal salt of 5-sulfoisophthalic acid is sodium salt of 5-sulfoisophthalic acid, the sodium element concentration in the non-volatile content of the sizing agent is preferably 100 ppm or more and 8000 ppm or less. The sodium element concentration in the non-volatile content of the sizing agent can be determined by elemental analysis using ICP.
[0037] The proportion of the alkali metal salt of 5-sulfoisophthalic acid in the monomers constituting the polyester resin (A) is not particularly limited, but can be, for example, from 1 mol % to 10 mol %.
[0038] The dicarboxylic acid monomer constituting the polyester resin (A) may include a dicarboxylic acid compound other than an alicyclic dicarboxylic acid compound and an alkali metal salt of 5-sulfoisophthalic acid (hereinafter referred to as "other dicarboxylic acid compound"). Examples of such dicarboxylic acids include isophthalic acid, terephthalic acid, oxalic acid, maleic acid, fumaric acid, succinic acid, and adipic acid. The ratio of the other dicarboxylic acid compound in the monomer constituting the polyester resin (A) is not particularly limited, but may be, for example, 30 mol% or more and 49 mol% or less. In addition, when the dicarboxylic acid monomer contains multiple types of other dicarboxylic acid compounds, the ratio of the other dicarboxylic acid compounds is the sum of the ratios of the multiple types of other dicarboxylic acid compounds.
[0039] Non-limiting examples of the polyester resin (A) according to this embodiment include copolymers of diethylene glycol, 1,4-cyclohexanedimethanol, sodium 5-sulfoisophthalate, and isophthalic acid, copolymers of diethylene glycol, ethylene glycol, 1,4-cyclohexanedimethanol, sodium 5-sulfoisophthalate, isophthalic acid, and terephthalic acid, copolymers of diethylene glycol, 1,4-cyclohexanedimethanol, sodium 5-sulfoisophthalate, 1,4-cyclohexanedicarboxylic acid, and isophthalic acid, and copolymers of diethylene glycol, sodium 5-sulfoisophthalate, 1,4-cyclohexanedicarboxylic acid, and isophthalic acid. The polyester resin (A) may be one type of compound or a mixture of multiple types of compounds.
[0040] In the sizing agent according to the present embodiment, the alicyclic group contained in at least one residue selected from the residues of alicyclic diols and the residues of alicyclic dicarboxylic acids plays a role in increasing the flexibility of the polymer chain of the polyester resin (A). High flexibility of the polymer chain of the polyester resin (A) is preferable from the viewpoint of preventing contamination of the roller by the sizing agent.
[0041] In the sizing agent according to the present embodiment, the residue of the alkali metal 5-sulfoisophthalate serves to impart hydrophilicity to the sizing agent because the sulfo group contained in the residue is an ionic functional group. The hydrophilicity of the sizing agent is preferable from the viewpoint of preventing contamination of the roller by the sizing agent.
[0042] The molecular weight of the polyester resin (A) according to the present embodiment is not particularly limited, but may be, for example, a weight average molecular weight of 5000 or more and 50000 or less. The weight average molecular weight of the polyester resin (A) may be determined, for example, by a method of GPC (gel permeation chromatography).
[0043] (Nonionic surfactant) The sizing agent according to the present embodiment may contain a nonionic surfactant (B). The nonionic surfactant (B) may be any nonionic surfactant commonly used in the art. The nonionic surfactant (B) may be one type of compound or a mixture of multiple types of compounds. It is preferable that the sizing agent contains the nonionic surfactant (B) from the viewpoint of preventing contamination of the roller by the sizing agent.
[0044] The nonionic surfactant (B) may be, for example, an alkylene oxide adduct of a compound having a hydroxyl group, or a derivative thereof (such as an esterified product). Examples of the compound having a hydroxyl group include, but are not limited to, aliphatic alcohols such as dodecyl alcohol, isododecyl alcohol, tetradecyl alcohol, tridecyl alcohol, secondary tetradecyl alcohol, and secondary tridecyl alcohol, and aromatic alcohols such as distyrenated phenol, tristyrenated phenol, and bisphenol A. Examples of the alkylene oxide include, but are not limited to, ethylene oxide and propylene oxide. Note that multiple types of alkylene oxides may be used in combination. The number of alkylene oxides added may be, but is not limited to, 8 moles or more and 30 moles or less per mole of the nonionic surfactant (B).
[0045] When the sizing agent contains a nonionic surfactant (B), the mass ratio of the polyester resin (A) to the total mass of the polyester resin (A) and the nonionic surfactant (B) is preferably 5% or more and 97% or less. When the mass ratio of the polyester resin (A) is 5% or more, it is advantageous in terms of bundling ability. Also, when the mass ratio of the polyester resin (A) is 95% or less, it is advantageous in terms of opening ability.
[0046] The nonionic surfactant (B) may be one type of compound or a mixture of multiple types of compounds.
[0047] (Epoxy resin) When the sizing agent according to the present embodiment contains a nonionic surfactant (B), the sizing agent may further contain an epoxy resin (C). The epoxy resin (C) may be any epoxy resin commonly used in the art. The epoxy resin (C) may be one type of compound or a mixture of multiple types of compounds. It is preferable that the sizing agent contains the epoxy resin (C) in terms of increasing the adhesion of the sizing agent to the fiber material.
[0048] Examples of the epoxy resin (C) include, but are not limited to, the jER (registered trademark) series (jER (registered trademark) 828, jER (registered trademark) 1001, jER (registered trademark) 1002, jER (registered trademark) 1004, etc.) manufactured by Mitsubishi Chemical Corporation, which are bisphenol-based epoxy resins, the NPES series (NPES301, NPES302, etc.) manufactured by Nanya Plastic Corporation, and the Sumiepoxy (registered trademark) series (Sumiepoxy (registered trademark) ELM-434, Sumiepoxy (registered trademark) ELM-100, etc.) which are amine-based multifunctional epoxy resins manufactured by Sumitomo Chemical Co., Ltd.
[0049] When the sizing agent contains a nonionic surfactant (B) and an epoxy resin (C), it is preferable that the mass ratio of the polyester resin (A) is 5% or more and 95% or less, the mass ratio of the nonionic surfactant (B) is 2% or more and 50% or less, and the mass ratio of the epoxy resin (C) is 2% or more and 65% or less, relative to the total mass of the polyester resin (A), the nonionic surfactant (B), and the epoxy resin (C). When the mass ratio of the epoxy resin (C) is 2% or more by mass, it is advantageous in terms of adhesion. Also, when the mass ratio of the epoxy resin (C) is 65% or less, it is advantageous in terms of preventing hardening over time of the reinforcing fiber bundle to which the sizing agent is applied.
[0050] The epoxy resin (C) may be one type of compound or a mixture of multiple types of compounds.
[0051] (Other Ingredients) The sizing agent according to the present embodiment may contain components other than the polyester resin (A), the nonionic surfactant (B), and the epoxy resin (C). Examples of such components include, but are not limited to, resins other than the polyester resin (A), preservatives, antistatic agents, antioxidants, ultraviolet absorbers, and defoamers (such as modified silicone).
[0052] In addition, as a typical embodiment when the sizing agent is used for the sizing treatment of a fiber material, a non-volatile component such as polyester resin (A) is diluted with a diluent (generally referred to as a sizing liquid). Such a diluent is also an example of another component. Examples of diluents include water (tap water, industrial water, ion-exchanged water, distilled water, etc.), acetone, methyl ethyl ketone, N-methyl-2-pyrrolidone, etc., but are not limited thereto. The concentration of the non-volatile component in the sizing agent in the embodiment in which the non-volatile component is diluted with a diluent is not particularly limited, but may be, for example, 10% by mass or more and 60% by mass or less. As described above, the non-volatile component of the sizing agent refers to the components that remain without volatilization after the sizing agent is heated in a hot air dryer at 105°C for 2 hours, and the concentration refers to the ratio of the mass of the non-volatile component in the sizing agent to the mass of the sizing agent.
[0053] [Method of producing sizing agent] The sizing agent according to the present embodiment can be obtained by mixing the polyester resin (A) and any optional components by a known method, for example, by adding water to the polyester resin (A) and any optional components while stirring at a temperature between 20° C. and 90° C. over a period of 5 hours.
[0054] [How to use sizing agent] The sizing agent according to the present embodiment is used in a sizing treatment of a fiber material. The sizing treatment is a treatment for attaching a sizing agent to a fiber material, and the method may be a method generally used in the art for attaching this type of sizing agent to a fiber material. That is, the immersion oiling method, the spray oiling method, the roller oiling method, the guide oiling method, and the like may be adopted. Note that when applying each method, the sizing agent may be appropriately diluted with a diluent such as water.
[0055] The amount of the sizing agent attached to the fiber material is not particularly limited. For example, it is preferable that the amount of the sizing agent attached to the entire fiber material to which the sizing agent is attached is 0.1 mass % to 3 mass %.
[0056] In addition, when the sizing agent according to the present embodiment is applied during the production of reinforcing fibers, reinforcing fibers having the sizing agent attached to the fiber material are obtained. This reinforcing fiber is an example of the reinforcing fiber according to the present invention. The fiber material is preferably an inorganic fiber, and in this case, the reinforcing fiber is an inorganic fiber having a sizing agent attached thereto. In addition, it is more preferable that the inorganic fiber is a carbon fiber or a glass fiber. These reinforcing fibers can be used in composite materials having resin, ceramic, metal, or the like as a matrix.
[0057] Other embodiments Regarding other configurations, it should be understood that the embodiments disclosed in this specification are illustrative in all respects and that the scope of the present invention is not limited thereto. A person skilled in the art would easily understand that appropriate modifications are possible without departing from the spirit of the present invention. Therefore, other embodiments modified without departing from the spirit of the present invention are naturally included in the scope of the present invention.
[0058] In particular, the sizing agent according to the present invention is characterized in that it contains a polyester resin (A) having a residue of an alkali metal salt of 5-sulfoisophthalic acid, but this is merely specified as a characteristic configuration for the purpose of claiming a patent to the extent that it has been confirmed that the effect is exhibited in the examples shown below. The effect of the present invention brought about by the above characteristic configuration is to prevent the roller from being contaminated by the sizing agent. In this regard, the inventors have speculated that the sulfo group contained in the residue of the alkali metal salt of 5-sulfoisophthalic acid is an ionic functional group, which contributes to the expression of the effect, and thus the sizing agent is given hydrophilicity, but this has not been proven, and the effect of the present invention has only been confirmed inductively from a comparison between the examples and the comparative examples. In other words, even if the residue is other than the residue of the alkali metal salt of 5-sulfoisophthalic acid, as long as it is a residue that can impart hydrophilicity to the sizing agent, the sizing agent containing the polyester resin having this residue may have the same effect as the present invention, but this has not been proven or confirmed. Therefore, the claims of this application do not intentionally intend to exclude from the technical scope of the present invention sizing agents that contain polyester resins having residues other than residues of alkali metal 5-sulfoisophthalic acid and that exhibit similar effects to those of the present invention.
[0059] The present invention can be a sizing agent for reinforcing fibers, characterized by containing a polyester resin (A) having, in its molecule, at least one residue selected from a residue of an alicyclic diol and a residue of an alicyclic dicarboxylic acid, and a residue of an alkali metal salt of 5-sulfoisophthalic acid.
[0060] In the sizing agent for reinforcing fibers, the alkali metal 5-sulfoisophthalic acid salt may be sodium 5-sulfoisophthalic acid salt, and the sodium element concentration in the nonvolatile matter may be 100 ppm or more and 8000 ppm or less.
[0061] The above-mentioned sizing agent for reinforcing fibers may further contain a nonionic surfactant (B).
[0062] The above-mentioned sizing agent for reinforcing fibers may further contain an epoxy resin (C). EXAMPLES
[0063] The present invention will be further described below with reference to examples, but the present invention is not limited to the following examples.
[0064] [Preparation of sizing agent] The following methods were used to prepare the samples shown in Table 1 in Examples 1 to 4. 13 and Reference Examples 1 to 7, and Sizing agents of Comparative Examples 1 to 4 shown in Table 2 were obtained.
[0065] (1) Raw materials (1-1) Polyester resin The following polyester resins were used. The polyester resins A-1, A-2, A-3, A-4, A-5, and A-6 correspond to the polyester resin (A) according to the above embodiment. The weight average molecular weight of each polyester resin is a value determined by the method of GPC (gel permeation chromatography).
[0066] (Polyester resin A-1) It is a copolymer of diethylene glycol (45 mol%), 1,4-cyclohexanedimethanol (5 mol%), sodium 5-sulfoisophthalate (4 mol%), and isophthalic acid (46 mol%), and has a weight average molecular weight of 9,000.
[0067] (Polyester resin A-2) It is a copolymer of diethylene glycol (48 mol%), 1,4-cyclohexanedimethanol (2 mol%), sodium 5-sulfoisophthalate (7 mol%), and isophthalic acid (43 mol%), and has a weight average molecular weight of 15,000.
[0068] (Polyester resin A-3) It is a copolymer of diethylene glycol (25 mol%), ethylene glycol (24 mol%), 1,4-cyclohexanedimethanol (1 mol%), sodium 5-sulfoisophthalate (9 mol%), isophthalic acid (30 mol%), and terephthalic acid (11 mol%), and has a weight average molecular weight of 6,000.
[0069] (Polyester Resin A-4) It is a copolymer of diethylene glycol (40 mol%), 1,4-cyclohexanedimethanol (10 mol%), sodium 5-sulfoisophthalate (1 mol%), and isophthalic acid (49 mol%), and has a weight average molecular weight of 45,000.
[0070] (Polyester Resin A-5) It is a copolymer of diethylene glycol (45 mol%), 1,4-cyclohexanedimethanol (5 mol%), sodium 5-sulfoisophthalate (3 mol%), 1,4-cyclohexanedicarboxylic acid (2 mol%), and isophthalic acid (45 mol%), and has a weight average molecular weight of 12,000.
[0071] (Polyester Resin A-6) It is a copolymer of diethylene glycol (50 mol%), sodium 5-sulfoisophthalate (2 mol%), 1,4-cyclohexanedicarboxylic acid (3 mol%), and isophthalic acid (45 mol%), and has a weight average molecular weight of 18,000.
[0072] (Polyester resin a-1) It is a copolymer of diethylene glycol (50 mol%), sodium 5-sulfoisophthalate (4 mol%), and isophthalic acid (46 mol%), and has a weight average molecular weight of 10,000.
[0073] (Polyester resin a-2) It is a copolymer of diethylene glycol (48 mol%), 1,4-cyclohexanedimethanol (2 mol%), and isophthalic acid (50 mol%), and has a weight average molecular weight of 8,000.
[0074] (1-2) Nonionic surfactants The nonionic surfactants shown below were used. All of the nonionic surfactants correspond to the nonionic surfactant (B) according to the above embodiment. However, the manufacturing method shown for each nonionic surfactant is only an example, and even if the nonionic surfactant is manufactured by a method different from the method exemplified below, the nonionic surfactant can be used in the examples. , reference example, And the results of the comparative examples remain unchanged.
[0075] (Nonionic surfactant B-1) Dodecyl alcohol and ethylene oxide were reacted in a molar ratio of 1:9 to obtain a nonionic surfactant B-1, which is an ethylene oxide adduct of dodecyl alcohol.
[0076] (Nonionic surfactant B-2) Isododecyl alcohol and ethylene oxide were reacted in a molar ratio of 1:12 to obtain a nonionic surfactant B-2, which is an ethylene oxide adduct of isododecyl alcohol.
[0077] (Nonionic surfactant B-3) Tetradecyl alcohol and ethylene oxide were reacted in a molar ratio of 1:7 to obtain a nonionic surfactant B-3, which is an ethylene oxide adduct of tetradecyl alcohol.
[0078] (Nonionic surfactant B-4) Tridecyl alcohol and ethylene oxide were reacted in a molar ratio of 1:15 to obtain a nonionic surfactant B-4, which is an ethylene oxide adduct of tridecyl alcohol.
[0079] (Nonionic surfactant B-5) Secondary tetradecyl alcohol and ethylene oxide were reacted in a molar ratio of 1:10 to obtain nonionic surfactant B-5, which is an ethylene oxide adduct of secondary tetradecyl alcohol.
[0080] (Nonionic surfactant B-6) Secondary tridecyl alcohol and ethylene oxide were reacted in a molar ratio of 1:9 to obtain nonionic surfactant B-6, which is an ethylene oxide adduct of secondary tridecyl alcohol.
[0081] (Nonionic surfactant B-7) Dodecyl alcohol was reacted with ethylene oxide and propylene oxide in a molar ratio of 1:2:6 to obtain the nonionic surfactant B-7, which is a random adduct of ethylene oxide and propylene oxide with dodecyl alcohol.
[0082] (Nonionic surfactant B-8) Tristyrenated phenol was reacted with ethylene oxide and propylene oxide in a molar ratio of 1:15:9 to obtain nonionic surfactant B-8, which is an ethylene oxide-propylene oxide random adduct of tristyrenated phenol.
[0083] (Nonionic surfactant B-9) Distyrenated phenol was reacted with ethylene oxide and propylene oxide in a molar ratio of 1:18:5 to obtain the nonionic surfactant B-9, which is an ethylene oxide-propylene oxide random adduct of distyrenated phenol.
[0084] (Nonionic surfactant B-10) Bisphenol A was reacted with ethylene oxide in a molar ratio of 1:18 to obtain a nonionic surfactant B-10, which is an ethylene oxide adduct of bisphenol A.
[0085] (Nonionic surfactant B-11) Tristyrenated phenol and ethylene oxide were reacted in a molar ratio of 1:30 to obtain nonionic surfactant B-11, which is an ethylene oxide adduct of tristyrenated phenol.
[0086] (Nonionic surfactant B-12) Dodecyl alcohol and ethylene oxide were reacted in a molar ratio of 1:5 to obtain a nonionic surfactant B-12, which is an ethylene oxide adduct of dodecyl alcohol.
[0087] (1-3) Epoxy resin The following epoxy resins were used. All of the epoxy resins correspond to the epoxy resin (C) according to the above embodiment.
[0088] (Epoxy resin C-1) The product is jER (registered trademark) 828 manufactured by Mitsubishi Chemical Corporation.
[0089] (Epoxy resin C-2) The product is jER (registered trademark) 1001 manufactured by Mitsubishi Chemical Corporation.
[0090] (Epoxy Resin C-3) The product is jER (registered trademark) 1002 manufactured by Mitsubishi Chemical Corporation.
[0091] (Epoxy Resin C-4) The product is jER (registered trademark) 1004 manufactured by Mitsubishi Chemical Corporation.
[0092] (Epoxy Resin C-5) It is NPES301 manufactured by NAN YA PLASTIC CORPORATION.
[0093] (Epoxy Resin C-6) It is NPES302 manufactured by NAN YA PLASTIC CORPORATION.
[0094] (Epoxy Resin C-7) The epoxy resin is Sumiepoxy (registered trademark) ELM-434 manufactured by Sumitomo Chemical Co., Ltd.
[0095] (Epoxy Resin C-8) The epoxy resin is Sumiepoxy (registered trademark) ELM-100 manufactured by Sumitomo Chemical Co., Ltd.
[0096] (1-4) Other ingredients The following were used as other components: D-1: Octyl palmitate D-2: Tridecyl stearate D-3: Acid-modified polyolefin resin Diluent: Ion-exchanged water
[0097] (2) Preparation of sizing agent Example 1 The raw materials were weighed out as follows: 14 parts by mass of polyester resin A-1, 20 parts by mass of nonionic surfactant B-1, 10 parts by mass of nonionic surfactant B-2, and 56 parts by mass of epoxy resin C-1. The weighed raw materials were mixed and stirred at 80° C. while gradually adding 300 parts by mass of ion-exchanged water as a diluent over a period of 5 hours to obtain the sizing agent of Example 1.
[0098] (Example 2 13, Reference examples 1-7, and Comparative Examples 1 to 4) The same method as in Example 1 was used except that the raw materials used were those listed in Tables 1 and 2 below. 13, Reference examples 1-7, And, the sizing agents of Comparative Examples 1 to 4 were obtained.
[0099] [Evaluation of sizing agents] Working Example , reference example, The following procedure was used to evaluate each of the examples and comparative examples. However, carbon fiber and glass fiber were used as fiber materials for evaluating the sizing agent. Both carbon fiber and glass fiber were commercially available fiber materials for resin reinforcement.
[0100] (1) Sodium concentration in non-volatile matter Working Example , reference example, Approximately 2 g of each of the sizing agents of the comparative example and the comparative example was weighed into a heat-resistant container, and the heat-resistant container was heated in a hot air dryer at 105° C. for 2 hours. The non-volatile content remaining in the heat-resistant container after heating was precisely weighed, wet-decomposed with a mixture of perchloric acid and nitric acid, and then subjected to elemental analysis by ICP to quantify the sodium concentration in the non-volatile content.
[0101] (2) Convergence Working Example , reference example, A sizing bath was filled with a sizing solution (non-volatile content concentration 4%) containing the sizing agent of each of the Examples and Comparative Examples, and a fibrous material (carbon fiber or glass fiber) was passed through the sizing bath to apply the sizing agent. The roll of the fibrous material after application of the sizing agent was set on a creel and unwound at a speed of 5 m per minute, and the state of the fibrous material passing through the roller immediately after unwound was observed. Depending on the observation results, the following were determined: Example: , reference example,The bundling ability of the fiber material brought about by the sizing agent of each of the examples of the comparative example was evaluated on a three-level scale of A to C. A: Almost no fiber material was found to be wound around the roller, and the passed fiber material was well-cohered. B: A small amount of fibrous material was found to be wound around the roller, but the fibrous material that had passed through was well held together. C: A large amount of fibrous material was wrapped around the roller, and the fibrous material that passed through was seen to break apart.
[0102] Here, whether or not the fiber material is well-cohered is judged by visual observation based on the criterion of whether or not the fibers are loose enough to leave gaps in the bundle of fiber material.
[0103] (3) Roller contamination Working Example , reference example, A sizing bath was filled with a sizing solution (non-volatile content concentration 4%) containing the sizing agent of each of the Examples and Comparative Examples, and a fibrous material (carbon fiber or glass fiber) was passed through the sizing bath to apply the sizing agent thereto for one day. During this operation, the state of the rollers that the fibrous material came into contact with immediately after passing through the sizing bath was observed. Depending on the observation results, the following were determined: Example 1, Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5, Comparative Example 6, Comparative Example 7, Comparative Example 8, Comparative Example 9, Comparative Example 10, Comparative Example 11, Comparative Example 12, Comparative Example 13, Comparative Example 14, Comparative Example 15, Comparative Example 16, Comparative Example 17, Comparative Example 18, Comparative Example 19 ... , reference example, The degree of roller contamination caused by the sizing agent of each of the examples and the comparative examples was evaluated on a five-level scale from A to E. A: After one day of operation, almost no fuzz or sticky matter was found adhering to the roller. B: After one day of operation, 1 to 4 pieces of fuzz were visible on the roller. Smooth operation was possible. C: After one day of operation, 5 to 9 fuzz strands were visible on the roller, and sticky material was observed on the roller. Smooth operation was possible. D: After one day of operation, 10 to 29 fuzz strands were visible on the roller, and sticky material was found on the roller. The roller needed to be cleaned several times, but this did not interfere with operation. E: After one day of operation, more than 30 fuzz strands were found to be attached to the roller by visual inspection, and a lot of sticky material was found to be attached to the roller. A problem occurred in which the textile material was wrapped around the roller. Maintenance was required to remove the textile material from the roller, and operational problems were recognized.
[0104] (4) Adhesiveness Working Example , reference example, A sizing solution (non-volatile content concentration 2%) containing the sizing agent of each of the examples of the comparative examples was prepared, and a fiber material (carbon fiber or glass fiber) was immersed in the sizing solution to apply the sizing agent. A fiber material was taken out from the fiber material to which the sizing agent was applied. Both ends of the fiber material were fixed to a square frame-shaped holder with adhesive so that the fiber material was in a tensed state. A matrix resin, which was a mixture of epoxy resin (epoxy equivalent 190, jER (registered trademark) 828 manufactured by Mitsubishi Chemical Corporation) and BF3 monoethylamine salt (boron trifluoride monoethylamine manufactured by Stella Chemifa Corporation) in a mass ratio of 100:3, was attached to the fiber material as resin droplets with a diameter of about 70 μm. The fiber material and the matrix resin were bonded by heating in an air atmosphere at 160° C. for 90 minutes to prepare a test piece.
[0105] Each sample piece was sandwiched between two blades, which were moved in the fiber axial direction at a speed of 5 mm per minute, and the maximum stress F generated when the resin droplets were peeled off from the fiber material by the blades was measured with a load cell. The interfacial shear strength τ was calculated using the measured value according to formula (6). The calculation of the interfacial shear strength τ (unit: MPa) according to the above procedure was carried out in Example 1. , reference example, For each example and comparative example, the measurement was carried out 20 times, and the average value was used as the measurement result.
number
[0106] In equation (6), F is the maximum stress (unit: kgf) generated when the resin droplet peels off from the carbon fiber, D is the diameter (unit: mm) of the carbon fiber used as the test piece, and L is the diameter (unit: mm) of the resin droplet in the test piece in the fiber axis direction.
[0107] Based on the obtained interfacial shear strength τ, , reference example, The adhesiveness of the sizing agent of each of the examples and comparative examples was evaluated on a four-level scale from A to D. A: The interfacial shear strength τ is 80 MPa or more. B: The interfacial shear strength τ is 70 MPa or more and less than 80 MPa. C: The interfacial shear strength τ is 60 MPa or more and less than 70 MPa. D: The interfacial shear strength τ is less than 60 MPa.
[0108] 〔result〕 Working Example , reference example, Tables 1 and 2 show the raw material composition of each example and comparative example, the fiber materials (carbon fiber or glass fiber) used in the evaluation, and the results of each evaluation.
[0109] Table 1: Evaluation results of sizing agents (Examples and reference examples ) [Table 1]
[0110] Table 2: Evaluation results of sizing agents (comparative examples) [Table 2] [Industrial Applicability]
[0111] The present invention can be used, for example, in the sizing process of textile materials.
Claims
1. A sizing agent for reinforcing fibers, comprising a polyester resin (A) having, in its molecule, at least one residue selected from a residue of an alicyclic diol and a residue of an alicyclic dicarboxylic acid, and a residue of an alkali metal salt of 5-sulfoisophthalic acid.
2. the alkali metal 5-sulfoisophthalic acid salt is sodium 5-sulfoisophthalic acid salt, 2. The sizing agent for reinforcing fibers according to claim 1, wherein the sodium element concentration in the non-volatile matter is 100 ppm or more and 8,000 ppm or less.
3. 2. The sizing agent for reinforcing fibers according to claim 1, wherein the polyester resin (A) has a residue of an alicyclic diol in the molecule.
4. The sizing agent for reinforcing fibers according to claim 1, wherein the content of the polyester resin (A) in the non-volatile matter is 5% by mass or more and 95% by mass or less.
5. The sizing agent for reinforcing fibers according to claim 1 , further comprising a nonionic surfactant (B).
6. 6. The sizing agent for reinforcing fibers according to claim 5, wherein the mass of the polyester resin (A) is 5% or more and 97% or less relative to the total mass of the polyester resin (A) and the nonionic surfactant (B).
7. The sizing agent for reinforcing fibers according to claim 5, further comprising an epoxy resin (C).
8. relative to the total mass of the polyester resin (A), the nonionic surfactant (B), and the epoxy resin (C), The proportion of the mass of the polyester resin (A) is 5% by mass or more and 95% by mass or less, The proportion of the mass of the nonionic surfactant (B) is 2 mass% or more and 50 mass% or less, and The sizing agent for reinforcing fibers according to claim 7, wherein the mass ratio of the epoxy resin (C) is 2 mass% or more and 65 mass% or less.
9. A reinforcing fiber having the sizing agent for reinforcing fibers according to any one of claims 1 to 8 attached thereto.
10. The reinforcing fiber according to claim 9, which is an inorganic fiber to which the sizing agent for reinforcing fibers is attached.
11. The reinforcing fiber according to claim 10, wherein the inorganic fiber is a carbon fiber or a glass fiber.
Citation Information
Patent Citations
Sizing agent for fibers
JP2009001954A
Carbon fiber sizing agent, carbon fiber strand and carbon fiber composite material
JP2015094039A
Composite yarn, fabric, and continuous reinforced fiber resin molding
JP2017110322A
Sizing compositions and fibrous articles sized therewith
US3546008A
Fiber sizing agent
WO2008143325A1
